Reform and Practice of Comprehensive Experiment Teaching in Water Pollution Control Engineering based on Project-Driven Approach - Jiao Chen; Mingjiang Peng; Yixin Lu; Xiaochun He; Xiaobo Yang (International Journal of Social Sciences and Public Administration, 2026)
Aiming at the prominent problems existing in the practical teaching of environmental engineering majors in application-oriented undergraduate colleges, such as outdated experimental contents, excessive proportion of verification experiments, disconnection from engineering practice, and insufficient student initiative, this paper takes the Comprehensive Experiment of Water Pollution Control Engineering course at Chengdu Technological University as the research object, and systematically explores the curriculum reform path based on Project-Based Learning (PBL). A project-driven teaching system oriented by real wastewater treatment engineering problems, supported by project clusters, and targeting competency cultivation was constructed. Four progressive experimental projects were designed: activated sludge performance diagnosis, aeration system optimization, process operation and control, and combined process design. Students’ experimental operation ability, engineering problem-solving ability, teamwork ability, and professional competence were significantly enhanced, forming practical teaching experience that can be promoted, which can provide useful reference for the project-driven teaching reform of environmental majors in similar institutions.